Perbedaan Pelayanan IGD Berdasarkan Triase Di RUmah Sakit Petrokimia Gresik Sebelum dan Sesudah Adanya Asuransi BPJS Kesehatan - Mudalifah, Efa; Ratnasari, Diah (Universitas Muhammadiyah Gresik, 2019)
Abstract Every hospital has emergency room (IGD) facility for 24 hours. The duty for this section is to give patirnt service with fast respond for emergency health case. In other hand, BPJS give an impact such as differences service in IGD Petrokimia Gresik Hospital. The purpose of this research is to know the different of disease based on triase and to get differences between pharmaceutical supplies in IGD Petrokimia Gresik after getting BPJS insurance. The method of this research is qualitative descriptive. Primer data is used as instrument research such as interview and direct observation. Meanwhile secondary data of this research is IDG documents. The result of this research showed that there was a differences between case or disease that happened in IGD Petrokimia Gresik,not only emergency case that handled in IGD after get BPJS insurance. The second result showed a differences between pharmaceutical supplies after BPJS insurance treatment. Patent medicine had changed to Generic medicine.